Gen-X Hamlets: Imitating the Dane to Find a Personal American Masculinity - Abele, Elizabeth (American Studies, 2010)
This essay examines the meanings associated with the figure of Hamlet in American popular culture, particularly as an ideal of American masculinity. Though this association between Prince Hamlet and American masculinity has a long history, this association became particularly strong in films of the 1990s. Though much critical attention has been paid to Hamlet references in big-budget films with middle-aged protagonists, less examined have been smaller-budget films that center on twentysomething protagonists struggling to find their own direction in post-feminist, post-Cold War, post-industrial American society. True Romance, Clueless, Beautiful Girls, Grosse Pointe Blank, Two Girls and a Guy and Best Men treat their references to Hamlet with wit, weaving them into the text in an offhand way, seamlessly mixing Shakespeare’s lines with contemporary dialogue–signaling more significant parallels between the two texts, in a dialogic relationship. This essay interrogates the versions of masculinity that Hamlet references are used to mark and to promote in these Gen-X films.